2019
DOI: 10.1186/s10194-019-0960-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging of the upper trapezius muscles – assessment of myofascial trigger points in patients with migraine

Abstract: BackgroundResearch in migraine points towards central-peripheral complexity with a widespread pattern of structures involved. Migraine-associated neck and shoulder muscle pain has clinically been conceptualized as myofascial trigger points (mTrPs). However, concepts remain controversial, and the identification of mTrPs is mostly restricted to manual palpation in clinical routine. This study investigates a more objective, quantitative assessment of mTrPs by means of magnetic resonance imaging (MRI) with T2 mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 43 publications
0
45
0
1
Order By: Relevance
“…Importantly, T 2 is well known to characterize a plethora of important disease processes such as iron deposition, fibrosis, edema, malignancy, and inflammation, among others. As a result, quantitative T 2 mapping with MRI has many applications, including assessment of neuro‐degenerative diseases and characterization of malignant lesions, detection of myocardial edema, detection of chronic rejection after heart transplant, detection of early cartilage degeneration, quantification of liver iron overload, and even identification of myofascial trigger points …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, T 2 is well known to characterize a plethora of important disease processes such as iron deposition, fibrosis, edema, malignancy, and inflammation, among others. As a result, quantitative T 2 mapping with MRI has many applications, including assessment of neuro‐degenerative diseases and characterization of malignant lesions, detection of myocardial edema, detection of chronic rejection after heart transplant, detection of early cartilage degeneration, quantification of liver iron overload, and even identification of myofascial trigger points …”
Section: Introductionmentioning
confidence: 99%
“…Second, the exact localization of stimulation was defined according to previous manual palpation performed to detect active or latent mTrPs. Manual palpation is considered the gold standard for the identification of mTrPs since decades (25, 66); however, novel techniques like qualitative magnetic resonance imaging (MRI) or quantitative MRI using T2 mapping might be capable of visualizing and determining mTrPs more objectively, thus paving the way for navigated rPMS interventions (11, 12, 67). Third, this study only involves a certain neck muscle, the trapezius muscle, as a structure being part of the TCC and only one muscle, the deltoid muscle, that is not supposed to be involved in the TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is unknown if neck pain directly contributes to migraine pain or is a consequence of it. Only a few MRI studies have reported hyperintense signals in the trapezius muscle in migraine patients (8,9), but the implications of these signal changes are not fully known. Thus, neck pain in migraine is, despite being a very frequent symptom, an under-investigated field of research in migraine.…”
Section: Introductionmentioning
confidence: 99%